2012
DOI: 10.1038/ki.2012.41
|View full text |Cite
|
Sign up to set email alerts
|

Impaired sodium excretion and salt-sensitive hypertension in corin-deficient mice

Abstract: Corin is a protease that activates atrial natriuretic peptide, a cardiac hormone important in the control of blood pressure and salt-water balance. Here we examined the role of corin in regulating blood pressure and sodium homeostasis upon dietary salt challenge. Radiotelemetry-tracked blood pressure in corin knockout mice on a high salt diet (4% sodium chloride) was significantly increased; however, there was no such change in similarly treated wild type mice. In the knockout mice on the high salt diet there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
73
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 40 publications
6
73
0
Order By: Relevance
“…This is a rather unusual situation described for only few genes: uromodulin (247,273,322) with a common noncoding variant within the GRE of the promotor and corin (76,272,(335)(336)(337)346) with a SNP in a coding region of the frizzle domain (R539C) found in 12% of African-Americans with hypertension. Common variants of APOL1 that confer resistance to trypanosomal infections in many regions of Africa are linked to the developpment of CKD (thus indirectly to hypertension) in African-American populations (250,340).…”
Section: Common Polymorphism With Strong Phenotypic Effectmentioning
confidence: 94%
“…This is a rather unusual situation described for only few genes: uromodulin (247,273,322) with a common noncoding variant within the GRE of the promotor and corin (76,272,(335)(336)(337)346) with a SNP in a coding region of the frizzle domain (R539C) found in 12% of African-Americans with hypertension. Common variants of APOL1 that confer resistance to trypanosomal infections in many regions of Africa are linked to the developpment of CKD (thus indirectly to hypertension) in African-American populations (250,340).…”
Section: Common Polymorphism With Strong Phenotypic Effectmentioning
confidence: 94%
“…ANP. In mice, disrupting the Corin gene abolished pro-ANP processing and caused spontaneous hypertension (Chan et al, 2005; Wang et al, 2012b), indicating that corin is the primary pro-ANP convertase in vivo . In humans, CORIN variants and mutations that impair corin activity have been identified in patients with hypertension and heart disease (Dong et al, 2013; Dries et al, 2005; Wang et al, 2012a; Wang et al, 2008; Zhang et al, 2014).…”
Section: Anp Biosynthesis and Processingmentioning
confidence: 99%
“…The three salt diets, despite having 10-fold increments of sodium, did not lead to any changes in serum sodium levels. An earlier study (21) using similar salt diets (0.3% NaCl and 4% NaCl) in mice also found that serum Na + , Cl − , and K + levels were unchanged in the two groups of mice. In the same study, Wang et al .…”
Section: Discussionmentioning
confidence: 66%